EFFECT OF QUALITY AND VALUE OF BEHAVIOR ATTENTION CUSTOMERS RESTAURANT BONCAFE STEAK MANYAR - Chen, Fei; Andajani, Erna; T, Juliani Dyah (Penerbit Atma Jaya Catholic University of Indonesia, 2018)
Nowdays in Indonesia, family restaurants gaining more popularity and become the most favourite place to eat for Indonesian families. The purpose of this study is to know whether service quality, food quality, and price value of Boncafe Steak and Ice Cream Manyar restaurant will effect customer satisfaction and will effect behavioral intentions of theconsumens that have visited and dine in the restaurant before. Aside from that this study also examine whether consumers satisfaction will make the consumers want to visit Boncafe Steak and Ice Cream Manyar restaurant again. The study of this research is basic research with causal purpose and quantitative approach. This study using quota sampling approach, which is a sampling technique that based on control characteristic in accordance with respondents characteristic that the researcher wants, and after that the researcher will determine quantity of the quota in order to fulfill minimum requirement to excute the analysis. As for the characteristics of the control set are respondends that have visit and dine in Boncafe Steak and Ice Cream Manyar and aged between 18-70 years old. Respondents that used on this study are 250 peoples. Result on this study showed that three hypotesis on this study are supported and two hypotesison this study are not supported. As for the hypotesis are customer satisfaction have positive effect to behavioral intention, service quality have positive affect to customer satisfaction,service qualiy have positive effect to behavioral intention, food quality have positive effect to customer satisfaction, and price value ratio have positive effect to customer satisfaction.